The Righteousness of God (Dikaiosunē Theou) and Verbal Genitives: A Grammatical Clarification - Burk, Denny (Journal for the study of the New Testament, 2012)
This article proposes to narrow the range of possible meanings for the phrase δɩκαɩοσύνη θɛου̑. Because δɩκαɩοσύνη is the nominalization of an attribute, we have to rule out of bounds any notion of δɩκαɩοσύνη θɛου̑ as a subjective or objective genitive. Once these two options are eliminated, the remaining possibilities for understanding the genitive are significantly narrowed. The article also suggests that Käsemann’s interpretation is still possible even when rendering the phrase as a simple possessive genitive—God’s own righteousness (though the genitive of source is still within the range of possible meanings as well). When interpreted as a possessive genitive, righteousness at its root is an attribute of the divine nature that can stand metonymically for God’s redemptive work through Christ. The article closes with a brief sketch of how this understanding would inform the exegesis of Rom. 1.17 and 3.21-26.